Evidence of the use of fruits in the complementary treatment of Anxiety and Diabetes - Costa, Joana Talita Galdino (2020)
Chronic non-communicable diseases such as Diabetes Mellitus and Anxiety are considered to be emerging diseases as they are increasingly prevalent in the population. On the other hand, together with the increase in the prevalence rates of these diseases, there is a constant search for low-cost alternative therapies and reduced adverse effects for the treatment of these comorbidities. Many of these therapeutic researches have investigated the use of fruits from many plants, due to the functional characteristics linked to them. Foods or ingredients with functional potential designate a positive impact on health, physical performance or mental state added to their nutritional value, since these ingredients contain bioactive compounds from vitamins, pigments and metabolites, which act on metabolic functioning. Brazil is a country with a vast diversity of fruits considered to be functional, this promotes an increased interest in new prospects regarding the potential use of these fruits in the treatment of various diseases. In view of this, the aim of this narrative review is to list fruits that have hypoglycemic and anxiolytic effects.